Georgius Cassander's irenical tract De officio pii viri (1561) : critical edition with two contemporary translations, incorporating Jean Hotman's Syllabus of irenical literature (1607), with a modern translation, commentary and introduction. (Radboud Studies in Humanities, 2015)
New Perspectives on Power and Political Representation from Ancient History to the Present Day offers a unique perspective on political communication between rulers and ruled from antiquity to the present day by putting the concept of representation center stage. It explores the dynamic relationship between elites and the people as it was shaped by constructions of self-representation and representative claims. The contributors to this volume - specialists in ancient, medieval, early-modern and modern history - move away from reductionist associations of political representation with formal aspects of modern, democratic, electoral, and parliamentarian politics. Instead, they contend that the construction of political representation involves a set of discourses, practices, and mechanisms that, although they have been applied and appropriated in various ways in a range of historical contexts, has stood the test of time.